Eighteen Proposals : Department of Ceramics & Glass. - Parson, Tim; Tan, Jack; Adamson, Glenn; Royal College of Art (s.l. : Royal College of Art, 2010)
Byrne, Edmond ; Doney, Ellie ; Eastwood-Bloom, Zachary ; Enemark, Hanne ; Eliot, Mylen ; Gomez, Tanya ; Hughes, Amy ; Kim, Sun Ae ; Kubiak, Maria ; Worthington, Bethan Lloyd ; McIntyre, Ian ; Mannheimler, Hanne ; Raw, Matthew ; Rodilosso, Luke ; Shiraya, Koji ; Todd, Martha ; Wightman, Annabel ; Brachlow, Heike
18 Proposals by Ceramics and Glass MA Students at the Royal College of Art 2010, foreword by Alison Britton
boek